A prayer before dawn [videorecording (DVD)] - Cole, Joe, 1988-; Mabklang, Pornchanok; Yimmumphai, Panya (Lionsgate, 2018)
The remarkable true story of Billy Moore, a young English boxer incarcerated in two of Thailand's most violent prisons. When the prison authorities allow Billy to participate in Muay Thai boxing tournaments, Billy goes from one savage fight to the next in a relentless, action-packed journey to preserve his life and regain his freedom. Shot in an actual Thai prison with a cast comprised of real inmates.